The Two Spanish Subjunctives: The Required and Default Subjunctives - Faulkner, Tris (Borealis – An International Journal of Hispanic Linguistics, 2022)
Standard Spanish grammar states that desideratives (querer que), directives (aconsejar que), purpose clauses (para que), causatives (hacer que), emotive-factives (alegrarse de que), negated epistemics (no creer que), dubitatives (dudar que), and modals (ser posible que) embed subjunctive complement clauses. However, in spite of these classifications, some predicates exhibit a certain degree of mood variation. For instance, emotive-factives can take indicative complements (Crespo del Río 2014; Faulkner 2021a). Similar variability between the moods may also come about in negated epistemic (Bolinger 1991), dubitative (Blake 1981), and modal clauses (Deshors and Waltermire 2019). I propose that such variation stems from the Spanish mood system involving a split between two types of subjunctives - one that is required in preference-based contexts, and another that is default and can be replaced by the indicative. I argue that, whereas preference-based expressions (desideratives, directives, purpose clauses, causatives) are inflexibly subjunctive, emotive-factives and verbs of uncertainty (negated epistemics, dubitatives, modals) may accept indicative if the speaker intends to add the affirmative or negated proposition to the common ground; i.e., if the speaker intends to assert the complement in question. I close these arguments by stating that assertion with the indicative is most likely to occur if the proposition (affirmative or negated) is informative (new or unknown to the addressee, important, contrastive, and/or highly probable).